2022
DOI: 10.3390/cells11142213
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Glucose Metabolism Promotes Senescence in Vascular Endothelial Cells

Abstract: Vascular aging is based on the development of endothelial dysfunction, which is thought to be promoted by senescent cells accumulating in aged tissues and is possibly affected by their environment via inflammatory mediators and oxidative stress. Senescence appears to be closely interlinked with changes in cell metabolism. Here, we describe an upregulation of both glycolytic and oxidative glucose metabolism in replicative senescent endothelial cells compared to young endothelial cells by employing metabolic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Multiple initiating triggers, namely oxidative stress, have been identified to drive stress-induced senescence in ECs 6,7 . Converging evidence supports the notion that gut microbiota, a yet underappreciated endocrine organ, can regulate oxidative-regulated host genes involved in endothelial cell biology 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple initiating triggers, namely oxidative stress, have been identified to drive stress-induced senescence in ECs 6,7 . Converging evidence supports the notion that gut microbiota, a yet underappreciated endocrine organ, can regulate oxidative-regulated host genes involved in endothelial cell biology 8 .…”
Section: Introductionmentioning
confidence: 99%
“…GAPDH, and pyruvate kinase) did not change significantly 56 ; and (3) glycolysis was increased with increased expression of lactate dehydrogenase A and decreased expression of pyruvate dehydrogenase kinase 1-4 57 . While the latter two studies both noted an increase in glucose consumption and lactate production, the former study did not see a correlation between these two changes and suggested glutaminolysis is the alternative energy source for senescent ECs 56 .…”
Section: Key Pathways Involved In Endothelial Senescencementioning
confidence: 92%
“…However, the main source of energy in senescent ECs is still a matter of debate. Different studies of replicative senescence in HUVECs have reported conflicting results, showing that (1) glycolysis decreased with a decline in the expression of nuclear factor E2-related factor 2 (NRF2) 54 , a regulator of endothelial proliferation and glycolysis 55 ; (2) the rate of glycolysis and the expression of glycolytic enzymes (hexokinase, LDH, aldolase, GAPDH, and pyruvate kinase) did not change significantly 56 ; and (3) glycolysis was increased with increased expression of lactate dehydrogenase A and decreased expression of pyruvate dehydrogenase kinase 1-4 57 . While the latter two studies both noted an increase in glucose consumption and lactate production, the former study did not see a correlation between these two changes and suggested glutaminolysis is the alternative energy source for senescent ECs 56 .…”
Section: Key Pathways Involved In Endothelial Senescencementioning
confidence: 99%
“…Senescent cells exhibit higher glycolytic activity and lactate production than youngest cells, alongside with an enhanced expression of lactate dehydrogenase A as well as increases in tricarboxylic acid cycle activity and mitochondrial respiration. The latter is likely due to the reduced expression of pyruvate dehydrogenase kinases (PDHKs) in senescent cells, which may lead to increased activity of the pyruvate dehydrogenase complex (Stabenow et al 2022 ).…”
Section: -Lactate Role In the Aging Process And The Role Of Mitochondriamentioning
confidence: 99%